Sztuka edukacji – przestrzeń muzeum i przedszkola jako środowisko kształcenia i wychowania do kultury - Sosnowska, Joanna (Nauczyciel wczesnej edukacji kreatorem środowiska edukacyjnego dziecka, 2016)
The aim of the work titled The art of education – the space of a museum and a kindergarten as the environment of education and training to culture is to present one of the ways of acquainting children with the cultural heritage of their “small homeland” – Łódź. The educational project titled “We visit museums of Łódź” becomes a part of education and training to culture of children/students as well as teachers because “entering” the space of a museum, in other words the space of art, requires the preparation of children/students to such a meeting. A significant role in that area is played by teachers; however, that is not the only thing demanded from them in that area. What is also required from the teacher is organizational competences related to a visit to a museum, a thing which teachers starting their career are prepared to do only to a small extent. The work presents examples of organizing classes in the museum environment as well as possibilities of continuing “meetings with the art” in the kindergarten environment. The project organized by teachers was conducted in the University of Łódź kindergarten. Here, in the school year of 2014/2015, a series of visits were organized to Łódź museums, in which the oldest children (aged 5 and 6) of that community took part.